Efficacy analysis of splint combined with platelet-rich plasma in the treatment of temporomandibular joint osteoarthritis - Wu, Chuan-Bin; Sun, Ning-Ning; Zhang, Dan; Wang, Qiang; Zhou, Qing (Frontiers in Pharmacology, 2022)
Objective: To evaluate splint combined with PRP for the treatment of temporomandibular joint osteoarthritis. Methods: Thirty-one patients with temporomandibular joint osteoarthritis who were treated with Splint combined with platelet rich plasma (PRP) from January 2021 through June 2021 at the Department of Oral and Maxillofacial Surgery, School of Stomatology, China Medical University (Shenyang, China) were retrospectively reviewed. All patients were asked to give VAS scores before and 6 months after treatment, and the maximum comfortable mouth opening was recorded. All data were analysed by the paired t-test using SPSS software, and P<0.05 indicated statistically significant differences. Results: Thirty-one patients (thirty-nine joints) successfully underwent Splint+PRP treatment. The mean pretreatment VAS score was 6.1, and the mean VAS score 6 months posttreatment was 4.1. The posttreatment VAS score was significantly lower than the preoperative VAS score (P < 0.05). The mean pretreatment maximum comfortable mouth opening (MCMO) was 27.6mm, and the mean MCMO 6 months posttreatment was 34.8 mm. The MCMO was significantly improved (P < 0.05). Conclusion: Splint + PRP is an effective way for treatment of temporomandibular joint osteoarthritis.